If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + 6x + 7x = -51 Combine like terms: 6x + 7x = 13x 1 + 13x = -51 Solving 1 + 13x = -51 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 13x = -51 + -1 Combine like terms: 1 + -1 = 0 0 + 13x = -51 + -1 13x = -51 + -1 Combine like terms: -51 + -1 = -52 13x = -52 Divide each side by '13'. x = -4 Simplifying x = -4
| 80x^4y+84x^3y^2-20x^2y^3= | | 2l+2w=218 | | x-7-8=-10 | | 3x-1=-9 | | 1x+2=-7 | | f(3)=2-4 | | 3x=8+2x | | 11-1-10x=10 | | 6j^3-125= | | 2x^3-9x-35=0 | | x-3=-x^2 | | 50=8+a-2 | | 0.02(6+-3)=0.04(t-2)-0.02 | | 5x(2-3x)(-6+4x)=0 | | 90x^4y+42x^3y^2-24x^2y^3= | | 0=1-6y+8 | | 5x+9=20x-15 | | .5(x-6)=10 | | (6x-5)= | | 4-2y/3=1 | | 27=7+3k-12 | | 9X+5Y=2 | | g-3=(g*g) | | g-3=-g^2 | | g-3=g | | 18=5(x-2)-(x-8) | | 3*3=3 | | x+(2x-2)+(6x-5)= | | 2(x+1)=6(x-2)+6 | | 1-n-5=12 | | 218=2(3)+2w | | 100x+3225=75x+3200 |